Green Synthesis and Characterization Of Silver Nanoparticles using Dadap Serep (Erythrina lithosperma) Leaves Extract as a Bioreductor - Albahi, Fairuz Hammad; Sutoyo, Suyatno; Tukiran, Tukiran (Departemen Kimia, 2026)
Silver nanoparticles (AgNPs) had been widely applied in various fields such as health, food, environment, catalysts, optics, and electronics. The synthesis of silver nanoparticles can be carried using a bottom-up method using by bioreductants derived from natural extracts (green synthesis). This study aims to describe the green synthesis of silver nanoparticles using a bioreductants from dadap serep (E. lithosperma) leaves extract and to determine its characteristics. The synthesis was carried out by varying the volume ratio of dadap serep leaves extract to silver nitrate solution at ratios of 1: 1, 1: 2, 1: 3, and 1: 4, followed by optimization at pH 9, 10, and 11. Characterization of the synthesized AgNPs was carried out using Ultra Violet-Visible (UV-Vis) spectrophotometer, Fourier Transform Infrared (FTIR) spectrophotometer, Particle Size Analyzer (PSA), Scanning Electron Microscopy (SEM), and X-Ray Diffraction (XRD). The results showed that the optimum synthesis reaction conditions occurred at a volume ratio of 1: 4 and pH 10. The synthesized silver nanoparticles had an average particle size of 92 nm (DI = 0.3124). The FTIR spectrum showed the presence of hydroxyl groups (3242,88 cm-1), aromatic C=C (1568.35 cm-1), C-O (1033.25 cm-1 ), Ag-O. (519.23 cm-1). The results of XRD analysis showed typical peaks of silver atoms at 2 q: 37.71o (111), 43.84o (200), 64.07o (220), 77.04o (311). SEM analysis showed that the silver nanoparticles had an irregular surface morphology. Thus, dadap serep (E. lithosperma) leaves extract has the potential to be used as a bioreductor for the synthesis of silver nanoparticles.